The effect of EMS, IFC, and TENS on patient-reported outcome measures for chronic low back pain: a systematic review and meta-analysis - Daniel Wolfe; Brent Rosenstein; Maryse Fortin (Frontiers in Pain Research, 2024)
IntroductionChronic low back pain (CLBP) is the leading cause of years lived with disability worldwide. Transcutaneous electrotherapies have been widely used to treat CLBP but, with the partial exception of transcutaneous electrical nerve stimulation (TENS), their effect on pain, disability, quality-of-life, and psychosocial outcomes have not been systematically reviewed. The purpose of this systematic review and meta-analysis was to clarify the overall effect of transcutaneous electrotherapies on patient-reported outcome measures (PROMs) in CLBP patients.MethodsFour databases and two study registries were searched for studies that utilized transcutaneous electrotherapies as a primary intervention for CLBP, compared against active or passive controls. Two reviewers independently extracted study data and assessed risk of bias. Studies were grouped by intervention vs. comparison, and by time of follow-up. Meta-analyses were conducted where appropriate.ResultsA total of 89 full-text were assessed for eligibility; 14 studies were included, with 6 in the meta-analyses (all TENS or mixed TENS). Pain: meta-analyses revealed no significant difference for TENS vs. active control, TENS vs. passive control, or mixed TENS vs. active control at post-intervention, nor for mixed TENS vs. active control at 1-month post-intervention. Interferential current (IFC) was more effective than active control (2 studies), while electromyostimulation (EMS) was generally superior to passive, but not active, controls (6 studies).DisabilityMeta-analyses revealed no significant difference for TENS vs. active control at post-intervention, mixed TENS vs. active control at post-intervention, or mixed TENS vs. active control at 1-month post-intervention. IFC was more effective than active control (2 studies), while the EMS results were mixed (6 studies). We were unable to perform meta-analyses for quality-of-life or psychosocial outcomes.ConclusionThere is moderate evidence that TENS is similar to all controls for improving pain and disability. There is limited evidence that IFC is superior to active controls for improving pain and disability. There is limited evidence that EMS is superior to passive but not active controls for improving pain, and similar to all controls for improving disability.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=452851, Identifier (CRD42023452851).